Navigating Uncertain Times: Comparative Analysis of Islamic Banking Financial Performance in Indonesia Before and During the Covid-19 Pandemic - Azwar Afandi; Dadang Hermawan (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
This study analyzes the comparison of the financial performance of Islamic banks in Indonesia before and during the Covid-19 pandemic. The population used in this study consists of Islamic Commercial Banks in Indonesia. The research method employed is quantitative research with a comparative approach using IBM SPSS Statistics 25 software. The data used are secondary data in the form of financial reports published by each company's website from 2018 to 2021. The results of this study indicate significant differences in CAR and ROA ratios between before and during the Covid-19 pandemic. However, there are no significant differences in NPF, OER, and FDR ratios between before and during the Covid-19 pandemic. Furthermore, there are significant simultaneous differences in financial performance before and during the Covid-19 pandemic. This comparative analysis sheds light on the dynamic nature of Islamic banking financial performance during the Covid-19 pandemic. The findings provide valuable insights for policymakers, bank regulators, and industry stakeholders in understanding the sector's resilience and the need for adaptive strategies during times of crisis.